(untitled) (The Pakistan Development Review, 2013)
Capital flight from Pakistan has remained one of the major concerns of policy makers, mainly because of the nature of private capital outflows; that is, whereas private citizens hold a large amount of foreign assets, the country’s burden of foreign debt continues to grow. Capital flight over and above normal levels raises serious concerns. Capital flight induces foreign donors to demand repatriation of private capital held abroad in return for their support. Previous studies have largely ignored the fact that illegal capital flow is a two way phenomenon. Private citizens’ foreign capital is brought into the country when time is opportune. Using the measure of trade misinvoicing, this paper finds that between 1972 and 2013 the (net) reverse capital flight in Pakistan was of the order of about 30 billion. To explain this phenomenon, the paper examines the evolution of Pakistan’s exchange and trade control regimes in four phases. It is found that reversed capital flight increased during liberal regimes when both current and capital accounts were liberalised, meaning that in the absence of strong regulatory bodies, private citizens could manipulate trade and exchange laws. The paper offers some specific policy recommendations to restrict cross-border movement of capital through illegal channels. JEL Classification: F21, F32, H26